Sarcoidosis – review of literature and three clinical cases - Raszeja-Kotelba, Barbara; Stępień, Bogumiła; Machowiak-Sęk, Ewa; Dadej, Ingrid; Woźniak, Tomasz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Sarcoidosis is a systemic granulomatous disorder including lymphatic adenopathy and lung, hepatic, cardiac, ocular, skin, neurological and musculoskeletal manifestations. The disease occurs in all ages. The origin of sarcoidosis remains unknown. The development of noncaseating granulomas is thought to be the result of the characteristic immune response. The diagnosis of sarcoidosis is based on the clinical presentation, radiographic examination and histological confirmation of noncaseating granulomas. We presented three of our patients with skin manifestation of sarcoidosis.